Fish diseases and strategies taken by the farmers in freshwater aquaculture at southwestern Bangladesh (Bangladesh Journal of Zoology, 2016)
To understand the present status of fish diseases and their remedial measures taken by the fish farmers, a questionnaire survey and Participatory Rural Appraisal (PRA) tools including Focus Group Discussion (FGD) were conducted in seven districts of Bangladesh. In total 196 farmers were interviewed and nine FGD sessions were conducted. Disease occurs immediately after stocking (24%) and during the rainy season (21%) followed by cold season (19%). Mortality, abnormal swimming and feeding behavior, unusual appearance, some localized lesions and reduced growth are the main clue to recognize the fish disease. The most frequently observed diseases were epizootic ulcerative syndromes (18.72%) followed by tail and fin rot (13.19%), red spot (11.49%), gill rot (9.36%), parasitic disease (8.93%), broken prawn antennae (7.23%), and other environmental and nutritional diseases. To cure these diseases, farmers applied the following treatments: lime and potash, liming, lime and salt, lime alone, salt and potash, antibiotics, various chemicals, high doses of vitamin C, complete water exchange, and transport to another pond. This study showed that diseases can play important roles in freshwater aquaculture, but this role is often not recognized due to a lack of knowledge and veterinary backstopping services.Bangladesh J. Zool. 44(1): 111-122, 2016